Predictors and Outcomes of Burnout in Primary Care Physicians - Joseph Rabatin; Eric Williams; Linda Baier Manwell; Mark D. Schwartz; Roger L. Brown; Mark Linzer (SAGE Publishing, 2016)
Objective: To assess relationships between primary care work conditions, physician burnout, quality of care, and medical errors. Methods: Cross-sectional and longitudinal analyses of data from the MEMO (Minimizing Error, Maximizing Outcome) Study. Two surveys of 422 family physicians and general internists, administered 1 year apart, queried physician job satisfaction, stress and burnout, organizational culture, and intent to leave within 2 years. A chart audit of 1795 of their adult patients with diabetes and/or hypertension assessed care quality and medical errors. Key Results: Women physicians were almost twice as likely as men to report burnout (36% vs 19%, P < .001). Burned out clinicians reported less satisfaction ( P < .001), more job stress ( P < .001), more time pressure during visits ( P < .01), more chaotic work conditions ( P < .001), and less work control ( P < .001). Their workplaces were less likely to emphasize work-life balance ( P < .001) and they noted more intent to leave the practice (56% vs 21%, P < .001). There were no consistent relationships between burnout, care quality, and medical errors. Conclusions: Burnout is highly associated with adverse work conditions and a greater intention to leave the practice, but not with adverse patient outcomes. Care quality thus appears to be preserved at great personal cost to primary care physicians. Efforts focused on workplace redesign and physician self-care are warranted to sustain the primary care workforce.